Entrepreneurship and Art Education Tourism: A Study on Results of Management Skills Training Program for Students - Nugraheni, Trianti; Budiman, Agus; Sukmayadi, Yudi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
Entrepreneurship, in the context of the development of art education tourism programs in higher education, is regarded as a serious concern in reflecting the role of universities in developing the tourism industry. This is considered as the universities’ efforts of innovation and creativity to improve the competitiveness of higher education goals through the development of entrepreneurship in the field of educational tourism. This paper discusses the role of tertiary institutions in developing educational tourism entrepreneurship, which in its implementation empowers potential students by providing entrepreneurship training for them to be able to manage art education tourism program events. The data were obtained by test and questionnaire were given to 30 students at Universitas Pendidikan Indonesia who were involved in the activities of entrepreneurial training programs in the management of tourism education through the art business. The program was established by cooperating with universities, the local government, as well as non-governmental institutions.